Fentanyl pharmacokinetics is not dependent on hepatic uptake by organic anion-transporting polypeptide 1B1 in human beings - Ziesenitz, Victoria C.; Skopp, Gisela; Weiß, Johanna; Haefeli, Walter E.; Mikus, Gerd (Basic & clinical pharmacology & toxicology, 2013)
A recent study investigating the pharmacokinetics of fentanyl in Sprague-Dawley rats suggested fentanyl to be a substrate of rat organic anion-transporting polypeptide Oatp. In human beings, the most important OATP for the pharmacokinetics of many drugs is OATP1B1. Therefore, genetic variants of OATP1B1 (SLCO1B1) might modulate fentanyl pharmacokinetics and efficacy in human beings. Sixteen healthy male and female volunteers, homozygous for SLCO1B1*1a (genetic wild-type) (n = 11) or *15 (deficient haplotype carrying the single-nucleotide polymorphisms rs2306283 and rs4149056 and exhibiting altered transport activity; n = 5), were included in this randomized crossover study. The participants received fentanyl (5 μg/kg) intravenously alone or with the OATP inhibitor rifampicin (600 mg single oral dose). The pharmacokinetics of fentanyl and norfentanyl were determined by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). In addition, fentanyl uptake in vitro was evaluated in OATP1B1 overexpressing HEK293 cells and compared to a mock-transfected cell line. In the clinical trial, fentanyl clearance was 18.8 ± 8.2 mL/min. kg in SLCO1B1*1a and 19.5 ± 1.8 mL/min/kg in SLCO1B1*15 carriers and not significantly different between the genotypes. During rifampicin, fentanyl clearance was 15.0 ± 4.4 mL/min/kg in SLCO1B1*1a and 16.7 ± 5.9 mL/min/kg in SLCO1B1*15 carriers (p > 0.5). In addition, in vitro data also indicate that fentanyl is not transported by OATP1B1. In conclusion, our data indicate that OATP1B1 has no impact on fentanyl pharmacokinetics in human beings.